2002
DOI: 10.1177/016344370202400506
|View full text |Cite
|
Sign up to set email alerts
|

Shifting frames of the Palestinian movement in US news

Abstract: In this research, we explore the conditions under which US news media coverage of the Palestinian movement for independence has shifted over time, in relation to changes in the movement and in the political and social contexts in which it has taken place. To measure shifts in media attention and media frames over time we examined the coverage of Palestinian issues in the New York Times and the Associated Press between 1984 and 1998. Media coverage increased and framing became more positive following two events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…In the literature, the period from 1987 to 1993 is marked as the first intifada (Ismail, 2010;Noakes and Wilkins, 2002) We included five Flemish newspapers that were published in the selected periods (see later). A preliminary research on one artificial week -composed according to a stratified sample with constructed weeks -showed that this sample was too small to identify significant findings.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, the period from 1987 to 1993 is marked as the first intifada (Ismail, 2010;Noakes and Wilkins, 2002) We included five Flemish newspapers that were published in the selected periods (see later). A preliminary research on one artificial week -composed according to a stratified sample with constructed weeks -showed that this sample was too small to identify significant findings.…”
Section: Methodsmentioning
confidence: 99%
“…Noakes and Wilkins (2002) studied the representation of Palestine's demands based on a sample of news published by the New York Times and the Associated Press news agency, generating, via deductive procedures, seven specific frames, which were classified into 'positive' and 'negative' frames for the Palestinian interests. The negative frames for the Palestinian movement are those that presented Palestinian as 'terrorists', 'violent', 'combatants' and as the 'cause of the problem'.…”
Section: Specific and Generic Framesmentioning
confidence: 99%
“…Some research has suggested that the press recast Palestinians as David against an Israeli Goliath (Liebes, 1992;Palmer, 1997;Zaharna, 1997), whereas other research suggests that the media imposed a ''cycle of violence'' narrative onto the conflict (Collins and Clark, 1992;Roeh and Cohen, 1992). Subsequent research shows that the news media continued to place most of the blame for the Intifada on the Palestinians (Noakes and Wilkins, 2002;Wu et al, 2002). Public opinion polls revealed that Americans continued to blame Palestinians despite sympathetic accounts in the press (Daniel, 1997), and pollsters' questions framed Israeli violence as a ''response'' to Palestinian violence (Gilboa, 1989).…”
Section: Us News Media: Israeli Response To Arab/palestinian Violencementioning
confidence: 99%
“…Whereas reporters praise Israeli officials for getting to the point, they report frustration with Palestinians who are not as forthcoming with relevant information (Dunsky, 2008). Even when Palestinians receive relatively greater press attention, some research shows that US news media are twice as likely to use Israeli sources than Palestinian sources (Noakes and Wilkins, 2002).…”
Section: Robert L Handleymentioning
confidence: 99%
See 1 more Smart Citation